2018
DOI: 10.1002/art.40390
|View full text |Cite
|
Sign up to set email alerts
|

Association of Defective Regulation of Autoreactive Interleukin‐6–Producing Transitional B Lymphocytes With Disease in Patients With Systemic Sclerosis

Abstract: Our findings provide new insights into mechanisms underlying defective B lymphocyte responses in patients with SSc and their contribution to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 49 publications
3
50
0
1
Order By: Relevance
“…In addition, these Th17 cells are likely to promote autoantibody production by B cells at least in a subgroup of patients. 89 This is supported by high levels of IL-6 and BAFF in SSc. 59…”
Section: To the Pathogenesis Of Systemic Sclerosis (Ssc)?mentioning
confidence: 89%
See 3 more Smart Citations
“…In addition, these Th17 cells are likely to promote autoantibody production by B cells at least in a subgroup of patients. 89 This is supported by high levels of IL-6 and BAFF in SSc. 59…”
Section: To the Pathogenesis Of Systemic Sclerosis (Ssc)?mentioning
confidence: 89%
“…IL‐17 levels are elevated in the blood of SSc patients compared with healthy individuals . Furthermore, several pro‐inflammatory cytokines including IL‐6 that promote Th17 cell differentiation are produced at high levels by immune cells including B cells . The indirect effects of IL‐17 on fibrosis are likely to be mediated by the effect of IL‐6 on fibroblast proliferation and increased production of pro‐fibrotic factors.…”
Section: Do Th17 Cells Contribute To the Pathogenesis Of Systemic Sclmentioning
confidence: 99%
See 2 more Smart Citations
“…inhibition of β‐catenin signalling, inhibition of tyrosine kinase and B‐cell depletion . The several studies demonstrated that the contribution of B cell and T cell in SSc development and pathogenesis. In addition to the acquired immunological reaction on SSc, the role of the innate immune system in the pathogenesis of SSc is now being increasingly recognized .…”
Section: Introductionmentioning
confidence: 99%